Pengemasan Atraksi Wisata Susur Sungai Klegung dengan Menggunakan Pendekatan Potensi Wisata - Arif Dwi Saputra (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
Community-based ecotourism development is an opportunity to develop tourism attractions that are almost unknown to tourists in general and will reduce the social-cultural impact for the community. The potential of the Klegung river that forms the river flow and the natural wealth of its riverside ecosystem makes the community take the initiative to open tourism destinations to provide benefits both economically and for the sustainability of existing water resources. The research that has been conducted using a qualitative descriptive method aims to analyze the potential of human resources, culture, flora and fauna, and attractions in accordance with the characteristics of Padukuhan Klegung. Having known the potential, then made attractive and appropriate attraction packages. keywords are required for computerization. Research and abstract title search made easy with these keywords